The comparison of use of antibiotics due to acute respiratory infections in the rural population of primary care in 2010 and 2017 - Zachara, Jarosław; Zachara, Radosław; Zachara, Norbert; Matuszczak, Agnieszka; Kłoda, Karolina (Journal of Education, Health and Sport, 2019)
Respiratory tract infections are the most common reason because of which patients report to a family doctor. The role of the family doctor is to assess both the symptoms suggesting the aetiology of infection, as well as performing additional tests, in order to make a definitive diagnosis. An increasing clinical problem is antibiotic resistance. Therefore, the objectives of this study were to assess and compare antibiotic use due to acute respiratory infections in the rural primary care population for over a 7-year period.A retrospective examination of electronic medical records covered 4355 declared patients in 2010 and 3959 patients declared in 2017. The analysis included advice - medical consultations due to acute respiratory infections, related or not related to the antibiotic prescription. In 2010, 2531 such consultations were given, and in 2017 - 1687.The results of our analysis indicate that in the surveyed rural population there was a decrease in both the frequency of consultations for respiratory infections (58.12% vs 42.61%) and the frequency of prescribing antibiotics / chemotherapeutics for this reason (50.8% vs 34, 6%). The type of antibiotic, which was most often used in the diagnosis of J06 (dominating both in 2010 and in 2017), has changed as well - from azithromycin to amoxicillin. The structure of diagnoses of respiratory tract infections systemized by ICD-10 has also been slightly changed.The reducing frequency of prescribing antibiotics as well as the change of the "first choice" antibiotic in the treatment of acute respiratory infections is a favorable trend and may result from the doctors' greater awareness of antibiotic resistance. Likewise, the change in the structure of diagnoses made by doctors from unspecified to specific ones may indicate greater awareness, resulting in treating specific diseases with targeted antibiotics. Further studies are needed to assess the choice of antibiotic therapy by the general practitioner.